(untitled) (Nigerian Journal of Technology, 2021)
Standard 1D3D mechanical cyclone with standard inlet velocity of 16m/s and cylinder diameter 0.1524m was modified using Downhill simplex method to develop four modified cyclone designs. Computational Fluid Dynamics (CFD) formulation involving model design, meshing, CFD simulation and postprocessing was carried out on the mechanical cyclones. ANSYS Fluent software was used for the CFD formulation using fine mesh of the default minimum mesh size of the CFD mesher. Cornstarch was used as inlet particulate matter. Reynolds Stress Turbulence Model (RSTM) was used to model the swirling turbulent flow while Discrete Phase Model (DPM) was used to track about 10,000 particles through the simulated cyclones. The DPM result of each mechanical cyclone was used to calculate it’s CFD, particle collection efficiency result. Standard 1D3D mechanical cyclone obtained particle collection efficiency result of 87.38% using cornstarch and default minimum mesh size for CFD simulation while modified 1D3D mechanical cyclone one (1) recorded the optimal CFD particle collection efficiency result among modified 1D3D mechanical cyclones with 94.00%. Its convergence iteration point also showed improvement in simulation time compared to the standard 1D3D mechanical cyclone. Consequently, it was concluded that, design modification in line with CFD formulation offers an alternative and powerful approach to modeling 1D3D mechanical cyclones performance.